Analisis Kesalahan Pembentukan Kata pada Media Sosial Instagram Akun @info_surabaya - R.A Naura Putri Fauziyah; Tariffa Fara Fadiya; Azzalea Syarifah Kamil; Fionita Tri Kusuma Wulandari; Taswirul Afkar (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explores spelling errors in posts by the Instagram account @info_surabaya, focusing on mistakes in spelling, language variations between Indonesian and English, and grammatical structures. Using a qualitative approach, the study analyzed text collected from selected posts within a specific timeframe. The findings reveal frequent issues such as inconsistent capitalization, incorrect use of loanwords, punctuation errors, and inappropriate word choices. Additionally, the influence of slang, regional languages, and informal writing styles was found to affect the quality of written communication. This research aims to provide practical recommendations to enhance awareness and adherence to proper Indonesian language usage, particularly on social media platforms.